Role of Physical Therapist in Stroke Rehabilitation: Review of International Procedures - Fatimh Abdulaziz Aljumah; Murtadha Hashim Alali; Abdulaziz Saad Alzahrani; Abeer Ali Mohammed Dhafeeri; Abdullah Ahmed Baydhi; Abdullah Ibrahim Alhejj; Samerh Twfiq Alsalem; Ali Saleh Albandar; Sadiyyah Yassen Alhumoud; Mustafa Hassan Musa Suwaylih; Abdulelah Sultan Alsafraa; Ali Saeed Al Hamqan (International Journal of Scientific Research and Innovative Studies, 2022)
Stroke is a leading cause of disability worldwide, often resulting in significant physical, cognitive, and emotional impairments. Physical therapy plays a crucial role in the rehabilitation and recovery of stroke survivors, focusing on restoring physical function, improving mobility, and enhancing overall quality of life. This review examines the role of physical therapy in stroke rehabilitation, highlighting current practices, evidence-based interventions, and the impact of physical therapy on functional outcomes and long-term recovery. Keywords: Stroke, physical therapy, rehabilitation, mobility, functional outcomes, recovery.